Disease associations between honeybees and bumblebees as a threat to wild pollinators - Fürst, M; McMahon, D; Osborne, J; Paxton, R; Brown, M (New Zealand Science Review, 2014)
​Emerging infectious diseases (EIDs) pose a risk to human welfare, both directly and indirectly, by affecting managed livestock and wildlife that provide valuable resources and ecosystem services, such as the pollination of crops. Honeybees (Apis mellifera), the prevailing managed insect crop pollinator, suffer from a range of emerging and exotic high-impact pathogens, and population maintenance requires active management by beekeepers to control them. Wild pollinators such as bumblebees (Bombus spp.) are in global decline, one cause of which may be pathogen spillover from managed pollinators like honeybees or commercial colonies of bumblebees. Here we use a combination of infection experiments and landscape-scale field data to show that honeybee EIDs are indeed widespread infectious agents within the pollinator assemblage. The prevalence of deformed wing virus (DWV) and the exotic parasite Nosema ceranae in honeybees and bumblebees is linked; as honeybees have higher DWV prevalence, and sympatric bumblebees and honeybees are infected by the same DWV strains, Apis is the likely source of at least one major EID in wild pollinators. Lessons learned from vertebrates highlight the need for increased pathogen control in managed bee species to maintain wild pollinators, as declines in native pollinators may be caused by interspecies pathogen transmission originating from managed pollinators. Nature 506: 364–366 (19 February 2014)